New evidence concerning the thermal history of Devonian and Carboniferous rocks in the South Portuguese Zone - Fernandes, Paulo (2014)
The Late Palaeozoic rocks of southern Portugal have a complex thermal history. Vitrinite reflectance determinations from 90 samples confirm that the organic maturity of Late Palaeozoic rocks in SW Portugal is very high, mainly corresponding to meta-anthracite coal rank. The optic fabric of vitrinite in oriented coal samples from the Brejeira Formation suggests maturation under simple, non-tectonic, burial conditions with peak temperatures being attained prior to Variscan deformation. The lack of any increase in vitrinite reflectance with depth through c. 1 km of section in borehole AC-1 is not consistent with conductive heat transfer and is interpreted as the result of late synorogenic to post-orogenic advective heating. This heating episode generated temperatures sufficiently high to produce levels of maturity corresponding to metaanthracite coal rank through much of the terrane now exposed, but not high enough to result in overprinting of the pre-deformation optic fabric of vitrinite in the thin coals. The slightly lower maturity of older, platformfacies rocks in the Aljezur–Bordeira area may reflect either deposition on a basement high followed by less burial than adjacent parts of the basin, or the area being the site of a sink for descending relatively cool fluids.